Identification of variables contributing to superovulation efficiency for production of transgenic prairie voles (Microtus ochrogaster) - Keebaugh Alaine C; Modi Meera E; Barrett Catherine E; Jin Chengliu; Young Larry J (BMC, 2012)
Abstract Background The prairie vole (Microtus ochrogaster) is an emerging animal model for biomedical research because of its rich sociobehavioral repertoire. Recently, lentiviral transgenic technology has been used to introduce the gene encoding the green fluorescent protein (GFP) into the prairie vole germline. However, the efficiency of transgenesis in this species is limited by the inability to reliably produce large numbers of fertilized embryos. Here we examined several factors that may contribute to variability in superovulation success including, age and parentage of the female, and latency to mating after being placed with the male. Methods Females produced from 5 genetically distinct breeder lines were treated with 100 IU of pregnant mare serum gonadotrophin (PMSG) and immediately housed with a male separated by a perforated Plexiglas divider. Ovulation was induced 72 hr later with 30 IU of human chorionic gonadotropin (hCG) and 2 hrs later mating was allowed. Results Superovulation was most efficient in young females. For example, females aged 6-11 weeks produced more embryos (14 +/- 1.4 embryos) as compared to females aged 12-20 weeks (4 +/- 1.6 embryos). Females aged 4-5 weeks did not produce embryos. Further, females that mated within 15 min of male exposure produced significantly more embryos than those that did not. Interestingly, there was a significant effect of parentage. For example, 12 out of 12 females from one breeder pair superovulated (defined as producing 5 or more embryos), while only 2 out of 10 females for other lines superovulated. Conclusions The results of this work suggest that age and genetic background of the female are the most important factors contributing to superovulation success and that latency to mating is a good predictor of the number of embryos to be recovered. Surprisingly we found that cohabitation with the male prior to mating is not necessary for the recovery of embryos but is necessary to recover oocytes. This information will dramatically reduce the number of females required to generate embryos for transgenesis in this species.